Analysis of the Cochrane Review: Incentives for Smoking Cessation. Cochrane Database Syst Rev. 2015;5:CD004307. - Vaz-Carneiro, António (2016)
Material incentives for alteration or reinforcement of healthy behaviours have been widely used in several health systems. These incentives, which are used in various contexts such as workplaces, health facilities or community programs, have been successfully implemented in smoking cessation programs. This systematic review - a third updated version of two published previously - sought to determine if a given set of incentives increased abstinence rates in smokers of medium and high risk (pregnant women). The authors searched several databases until December 2014: the Cochrane Tobacco Addiction Group Specialised Register, MEDLINE, EMBASE, CINAHL and PsycINFO. Two trials published in 2105 were included. The main results were:- In mixed populations (medium risk) six months after the onset there is a greater probability of withdrawal in patients subject to incentives. Direct payments to smokers - through different forms - were particularly effective (North American studies);- In populations of pregnant women (high risk), incentives caused a higher abstinence rate either during pregnancy or in the long term (up to 24 weeks postpartum).The authors conclude that the incentives appear to be effective in increasing the rate of smoking cessation in medium-risk as well as high-risk populations (e.g. pregnant women).